Healthcare experience quality: an empirical exploration using content analysis techniques. Issue 3 (15th June 2015) - Ponsignon, Frederic; Smart, Andi; Williams, Mike; Hall, Juliet
Abstract : Purpose: – The purpose of this paper is to set out to explore how cancer patients and their carers perceive and evaluate the healthcare experience in order to develop and validate a classification framework for experience quality in healthcare. Design/methodology/approach: – The empirical work is centred on the systematic analysis of 200 cancer patient stories published on an independent healthcare feedback web site. Using the critical incident method, the authors captured 1, 351 experience quality data items. Three judges independently sorted and classified these data items. Findings: – The authors identify and describe 22 main categories and 51 sub-categories that underlie the experience quality concept in healthcare and present them in a classification framework. The framework is informed through the categorisation of direct, indirect, and independent interactions. It also suggests a relationship between experience quality and satisfaction and loyalty behaviours. Research limitations/implications: – This study provides researchers with a foundation for the further development and validation of a measurement scale for experience quality in healthcare. Practical implications: – The framework assists managers and healthcare professionals with the definition, evaluation, and improvement of the quality of the experience of patients and their carers. Originality/value: – The main contributions of this study lie in: first, a comprehensive classification framework for experience quality in healthcare; second, dimensions that extend existing health service quality models; third, dimensions that contextualise the generic concept of customer experience quality to healthcare.